Effects of Out-of-School Exposure to English Language Learning - Vi Thanh Son; Joost van de Weijer (Journal of Linguistics and Language Teaching)
The out-of-school exposure to a foreign language has been found to enhance the development of lexical and grammatical knowledge of that language. In this study, we compared how English is used or encountered in out-of-school contexts in different contexts for Vietnamese and Swedish groups, and investigated whether out-of-school exposure to English as a foreign language had an impact on the learning outcomes in a group of Vietnamese children and another group of Swedish children. A demographic questionnaire and a test of procedural and declarative knowledge of English third-person singular -s were distributed to the children. Correlation coefficients between the eight demographic variables and the tests separated by the two groups of participants were analyzed. The results show that pupils’ estimated out-of-school exposure was significantly correlated with the Vietnamese children’s lexical repertoire, but not with their procedural or their declarative knowledge.